From Job-Based Pay to Skill-Based Pay in Unionized Establishments: A Three-Plant Comparative Analysis - Mericle, Kenneth; Kim, Dong-One (Relations industrielles / Industrial Relations, 1999)
Analyzing the experiences of three unionized manufacturing firms in North America, this paper examines two relatively unexplored issues in the previous literature: skill-based pay in unionized organizations and the transition from job-based pay (JBP) to skill-based pay (SBP). The three cases showed substantial uariety, particularly in the areas ofpractical detalls of SBP and the work System in which SBP operates. The cases show that SBPcan be successfully designed and implemented in older unionized workplaces with long-standing Tayloristic pay practices and strong contract language. Specifically, it was found that SBP can be introduced even where numerous job classifications are retained and that seniority rights are not inconsistent with an effective SBP System.